2016
DOI: 10.1177/0306624x16643786
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Self-Control in Late Adolescence: An Analysis of Trajectories and Predictors of Change Within Trajectories

Abstract: Gottfredson and Hirschi argue that parenting is the primary source of self-control. Research on the etiology of self-control has provided partial support for this proposition. Studies have shown parenting is an important determinant of self-control; however, research has also shown that other social and biological/genetic factors also influence the development of self-control. The current study contributes to the literature by examining the possibility that sources of self-control may vary across subgroups, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…This view was congruent with that of Piccolo et al's (2019) research showing that the adverse effect of a poor family factor on adolescents' inhibitory control was moderated by school climate. In a similar vein, Jo and Armstrong (2018) found that parenting and school factors may synchronously predict the development of adolescents' self‐control in a 6‐year longitudinal study. In contrast, adolescents living in a negative school climate environment are less likely to establish positive social connections among parents, teachers, and peers when they encounter poor parental supervision.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This view was congruent with that of Piccolo et al's (2019) research showing that the adverse effect of a poor family factor on adolescents' inhibitory control was moderated by school climate. In a similar vein, Jo and Armstrong (2018) found that parenting and school factors may synchronously predict the development of adolescents' self‐control in a 6‐year longitudinal study. In contrast, adolescents living in a negative school climate environment are less likely to establish positive social connections among parents, teachers, and peers when they encounter poor parental supervision.…”
Section: Introductionmentioning
confidence: 82%
“…A high‐level school climate, a positive factor from the school system, may ameliorate the negative impact of poor parental supervision from the family system on self‐control (Burt, 2020; Orkibi & Ronen, 2015). Even when poor parental supervision is high, adolescents living in a positive school climate may have more opportunities to learn impulse inhibition from their friends, teachers, and school norms, thus cultivating a higher level of self‐control (Jo & Armstrong, 2018; M. T. Wang et al, 2013). This view was congruent with that of Piccolo et al's (2019) research showing that the adverse effect of a poor family factor on adolescents' inhibitory control was moderated by school climate.…”
Section: Introductionmentioning
confidence: 99%
“…When recognizing how street gangs can facilitate crime by reducing its difficulty, a point we return to shortly, Gottfredson and Hirschi (1990, p. 159, emphasis in original) stated that, “[T]his does not mean that they learn lack of self‐control in such groups.” Yet, there are legitimate questions surrounding the veracity of this statement. There is mounting evidence that levels of self‐control decline as a result of associating with delinquent peers (Burt et al., 2006; Jennings et al., 2013; Jo & Armstrong, 2018; Meldrum & Hay, 2012; Meldrum et al., 2012; Ray et al., 2013). Dishion and colleagues (1996, 2010) referred to delinquent peer groups, but especially gangs, as contexts for deviancy training, a socialization process that shares many of the core features of social learning theory (Akers, 2009).…”
Section: Criminal Groups In Self‐control Perspectivementioning
confidence: 99%
“…Although the relationship between the elements put forth by the social learning theory and deviant behavior has been extensively researched for decades, it warrants further attention concerning how specific social learning theory variables (e.g., delinquent peer affiliation as a measure of differential association) are associated with low self-control (Huijsmans et al, 2021;Jo & Armstrong, 2018;Meldrum & Hay, 2012;. Additionally, further attention is needed in understanding the explanatory power of Akers (1998) SSSL theory of crime and deviance wherein the basic assumption is that social learning is the primary process linking social structure (USWP) to individual behavior (deviance.)…”
Section: Current Studymentioning
confidence: 99%